Prenatal stress and genetic risk: How prenatal stress interacts with genetics to alter risk for psychiatric illness. (April 2018) - Abbott, Parker W.; Gumusoglu, Serena B.; Bittle, Jada; Beversdorf, David Q.; Stevens, Hanna E.
Highlights: Eighteen human and sixteen animal studies on prenatal stress interaction with genetic variants were reviewed. Maternal serotonin transporter genetics interact with prenatal stress in effects on offspring symptoms. Offspring serotonin, dopamine and stress physiology related alleles interact with prenatal stress. Whole-genome approaches and maternal physiology and genetics analyses will be high yield for this field in future work. Abstract: Risk for neuropsychiatric disorders is complex and includes an individual's internal genetic endowment and their environmental experiences and exposures. Embryonic development captures a particularly complex period, in which genetic and environmental factors can interact to contribute to risk. These environmental factors are incorporated differently into the embryonic brain than postnatal one. Here, we comprehensively review the human and animal model literature for studies that assess the interaction between genetic risks and one particular environmental exposure with strong and complex associations with neuropsychiatric outcomes—prenatal maternal stress. Gene-environment interaction has been demonstrated for stress occurring during childhood, adolescence, and adulthood. Additional work demonstrates that prenatal stress risk may be similarly complex. Animal model studies have begun to address some underlying mechanisms, including particular maternal or fetal genetic susceptibilities that interact with stress exposure and those that do not. More specifically, the genetic underpinnings of serotonin and dopamine signaling and stress physiology mechanisms have been shown to be particularly relevant to social, attentional, and internalizing behavioral changes, while other genetic factors have not, including some growth factor and hormone-related genes. Interactions have reflected both the diathesis-stress and differential susceptibility models. Maternal genetic factors have received less attention than those in offspring, but strongly modulate impacts of prenatal stress. Priorities for future research are investigating maternal response to distinct forms of stress and developing whole-genome methods to examine the contributions of genetic variants of both mothers and offspring, particularly including genes involved in neurodevelopment. This is a burgeoning field of research that will ultimately contribute not only to a broad understanding of psychiatric pathophysiology but also to efforts for personalized medicine.